South Africa-Africa trade: Continental Free Trade Area - Tsitsi Effie Mutambara (Economics and Econometrics Research Institute (EERI), 2024)
South Africa-Africa trade was examined for 2001-2021 and results show that Africa is an important market for South Africa's manufactured products and there is ease of market access for these products; its trade with Africa is highly complementary; and it has strong trade linkages with Africa's regional groups. Current South Africa-Africa trade is a foundation South Africa could utilise to consolidate, broaden and strengthen its role in intra-Africa trade with the AfCFTA in place as more complementary trade opportunities emerge; markets open more and current trade linkages with regional groups strengthen as trade barriers are reduced further; and regional value chains and production clusters initiatives emerge as market access improves with new and dynamic comparative advantages emerging.
Keywords: F12; F14; 330; Revealed trade barrier index; Trade complementarity; Trade intensity